A survey on pairwise mutually permutable products of finite groups - Ballester-Bolinches, A.; Beidleman, J.C.; Heineken, H.; Pedraza-Aguilera, M.C. (Algebra and Discrete Mathematics, 2009)
In this paper we present some recent results about pairwise mutually permutable products and classes of groups related to the saturated formation of all supersoluble groups.